Antimicrobial usage and its quantification for neonatal sepsis at a tertiary care hospital neonatal intensive care unit - Kumari, Manjari; Chatterjee, Suparna; Som, Tapas; Chattopadhyay, Pinaki (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Antimicrobial therapy for neonatal sepsis is challenging as its judicious use can save neonates while its inappropriate use can lead to rapid emergence of resistant strains. Quantification of consumption of antimicrobial agents (AMA) has not been undertaken in Indian neonatal intensive care units (NICU) setting. This prospective observational study evaluated the antimicrobial prescribing pattern and quantified its consumption in clinically suspected neonatal sepsis (NS) cases. Methods: Clinically suspected NS cases admitted over study period of 18 months in a tertiary care level III NICU were enrolled. Data of antimicrobials prescribed, its consumption, culture sensitivity profile of organisms isolated were collected.Consumption was quantified by computing the days of therapy (DOT) per 1000 patient-days (PD). Results: 150 clinically suspected NS cases were enrolled; 37.33% were culture positive. The most common AMA prescribed were netilmicin (94.67%), piperacillin-tazobactam (88.67%). Only 0.67% cases received reserve antimicrobials like colistin, vancomycin and linezolid. 58% received 2 AMA, 39.33% received ≥3 agents. Total antimicrobial consumption was 614.86 DOT/1000 PD and 21.68 DOT/ neonate. Statistically significant difference in total AMA consumption amongst culture positive versus negative cases (p <0.001) was observed but difference was not significant in EOS versus LOS (p=0.95). Conclusion: Usage of antimicrobials for neonatal sepsis was guided by sensitivity pattern of local prevalent flora and clinical response. Usage of reserve antimicrobials were restricted. However, consumption of AB was higher compared to developed countries and we intend to use the study outcome data for antibiotic stewardship program to reduce antibiotic consumption and modify prescribing trends at the study setting.